Sosialisasi Kurikulum Merdeka Belajar dan Penguatan Literasi di Sekolah Mitra MIN 2 Nagan Raya - Khadijah (Akademi Farmasi YPPM Mandiri, 2022)
The independent learning curriculum is a renewal in the world of education so that education in Indonesia is for the better. The independent learning curriculum is a new breakthrough in this digital era. Teachers are required to be able to understand the demands of the digital era. Teachers must always be diligent in literacy to access the era of technological progress. Literacy is an activity or activity to further cultivate reading and writing movements. Literacy skills must continue to be honed to train teachers' thinking skills. For example, by often do the writing, the ability to meditate will be smooth. The problem is that in writing it is difficult to get ideas for the teacher to write. The feeling of fear writing in the wrong way often comes to the teachers’ minds. This also causes teachers to be less motivated to write because they do not know easy writing techniques so that writing becomes interesting. In this regard, training and assistance in strengthening literacy were carried out in this case writing literacy using the relay method in Min 2 Nagan Raya, Parom Village, Nagan Raya Regency. The teacher participated in this activity enthusiastically and cheerfully. This can be seen from the positive results of the teacher's worksheets in writing. 85% gave a very good response and 15% gave a good response. The materials and assistance provided in the training help teachers write better essays. Teachers also have competence in accessing materials contained in curriculum webs for their own learning such as teaching materials, learning media, lesson plans and etc.